Cesare Cases: l’arte della recensione - Raffaeli, Massimo (L'ospite ingrato, 2024)
In his life Cesare Cesare wrote hundreds of book reviews, which he spread across the most diverse magazines and newspapers, from Elena Croce’s «Spettatore italiano» to the literary supplement of the newspaper «Il Sole 24 ore». Although he never actually theorised the art of book reviewing, he did, on one specific occasion, describe its compositional dynamics. The subject of this essay is his text, entitled Ai recensori and published in the first issue of the monthly journal «L’Indice dei libri del mese» (1984). Here Cases outlined the principles that should structure a good review: clarity, selection, summary and motivation.